2018
DOI: 10.3389/fimmu.2018.00565
|View full text |Cite
|
Sign up to set email alerts
|

Human Endothelial Cells Modulate CD4+ T Cell Populations and Enhance Regulatory T Cell Suppressive Capacity

Abstract: Endothelial cells (ECs) line the luminal surface of blood vessels and have an active role in the recruitment of leukocytes, including immune cell activation. Regulatory T cells (Tregs) are immune suppressor cells that maintain peripheral tolerance and must interact with the endothelium as they traffic into tissue. We hypothesized that human ECs could modulate Tregs and their suppressor function. Cocultures of CD4+ T cells with human umbilical vein ECs (HUVECs) or dermal microvascular ECs (HDMECs) were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…Prominent roles of CD4 + T cells in chronic diseases have been reported in previous studies ( 52 , 53 ). Our colleagues showed that massive CD4 + T lymphocyte infiltration was observed in the fibrotic kidneys of patients and UUO mice ( 54 ).…”
Section: Discussionsupporting
confidence: 64%
“…Prominent roles of CD4 + T cells in chronic diseases have been reported in previous studies ( 52 , 53 ). Our colleagues showed that massive CD4 + T lymphocyte infiltration was observed in the fibrotic kidneys of patients and UUO mice ( 54 ).…”
Section: Discussionsupporting
confidence: 64%
“…The immunosuppressive function of Treg is modulated by plenty of mechanisms, including direct engagement with cells through costimulatory signals via OX40, PD-1 and their ligands and indirectly by cytokine through TGF-β and IL-10 34. Endothelial cells (ECs) exert important effect on immunocyte recruitment and activation.…”
Section: The Role Of Pd-1/pd-l1 Axis In Treg Development and Functionmentioning
confidence: 99%
“…Thus, we speculate that the interaction between Tregs and macrophages may be involved in tissue repair and pulmonary fibrosis induced by radiation, which warrants further investigation. Additionally, the interaction between Tregs and endothelial cells (ECs) has attracted special attention due to its potential involvement in the regulation of inflammation (91)(92)(93). Human umbilical vein endothelial cells co-cultured with Tregs show a diminished capacity to respond to lipopolysaccharide in terms of adhesion molecule expression and pro-inflammatory cytokine production (e.g., monocyte chemoattractant protein-1 and IL-6), suggesting a protective role of Tregs during inflammation (93).…”
Section: Therapeutic Implications and Future Directionsmentioning
confidence: 99%